Enhanced Migratory Capacity of T Lymphocytes in Severe Chagasic Patients Is Correlated With VLA-4 and TNF-α Expression - Berbert, Luiz Ricardo; González, Florencia Belén; Villar, Silvina Raquel; Vigliano, Carlos; Lioi, Susana; Beloscar, Juan; Bottasso, Oscar Adelmo; Silva-Barbosa, Suse Dayse; Savino, Wilson; Pérez, Ana Rosa (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi infection in humans leads to progression to chronic chagasic myocarditis (CCM) in 30% of infected individuals, paralleling T cell-inflammatory infiltrates in the heart tissue. T cell trafficking into the hearts of CCM patients may be modulated by in situ expression of chemotactic or haptotactic molecules, as the chemokine CXCL12, the cytokine tumor necrosis factor-alpha (TNF-α) and extracellular matrix proteins, such as fibronectin. Herein we evaluated the expression of fibronectin, CXCL12 and TNF-α in the myocardial tissue of T. cruzi-seropositive (asymptomatic or with CCM), as well as seronegative individuals as healthy controls. Hearts from CCM patients exhibited enhanced expression of these three molecules. CXCL12 and TNF-α serum levels were also increased in CCM individuals. We then evaluated T lymphocytes from chronic chagasic patients by cytofluorometry, in terms of membrane expression levels of molecules involved in cell activation and cell migration, respectively HLA-DR and the VLA-4 (very late antigen-4, being one integrin-type fibronectin receptor). Indeed, the expression of HLA-DR and VLA-4 was enhanced on T lymphocytes from chagasic patients, especially in the CCM group. To further approach the dynamics of T cell migratory events, we performed fibronectin, TNF-α and CXCL12-driven migration. Peripheral blood mononuclear cells (PBMCs) and T cells from CCM patients presented an ex- vivo enhanced migratory capacity driven by fibronectin alone when this ECM protein was placed in the membrane of transwell migration chambers. When TNF-α was previously placed upon fibronectin, we observed a further and significant increase in the migratory response of both PBMCs and T lymphocytes. Overall, these data suggest the existence in patients with chronic Chagas disease of a cardiac inflammatory infiltrate vector that promotes the recruitment and accumulation of activated T cells, driven in part, by enhanced tissue expression of fibronectin and TNF-α, as well as the respective corresponding VLA-4 and TNF receptors.